Prevalence And Risk Factors Of Stunting Among Toddlers In Urban And Rural - Nashira, Illiyin Tri; Kusnandar, Kusnandar; Sukamto, Ika Sumiyarsi (Jurnal Kesehatan Manarang, 2024)
The high prevalence of stunting in Sungai Penuh City makes it necessary to identify the causes of stunting in a local context by looking at the classification of residence. Stunting that is not resolved will have an impact on the Lost Generation in the future. This cross-sectional study with data from the Indonesian Nutrition Status Survey in 2022 aims to analyze the prevalence and risk factors for stunting in toddlers in rural and urban areas, so that the problem of chronic malnutrition can be resolved according to the conditions where toddlers live. Data collection was conducted in August-September 2022, while data requests were made in January 2024. The sample was 395 toddlers living in Sungai Penuh City. To see the relationship between the dependent variable and the independent variable, the Chi-square test was performed and to see the relationship between the dependent variable and the independent variable simultaneously, the Logistic Regression test was performed using the IBM SPSS statistics version 25 application software. The results of this study show that the prevalence of stunting in urban areas is higher than in rural areas, but there are no differences in risk factors for stunting, and overall rural-urban in Sungai Penuh City on the variable of birth length with OR (95% CI) 2.30 and maternal education with OR (95% CI) 2.22 shows the risk of having stunted children (p-value <0.005). This study concludes that there are differences in prevalence between rural and urban areas, but there are no differences in the risk factors that cause stunting in toddlers.